2014
DOI: 10.5770/cgj.17.106
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Level of Care Patients in Hospitals: What Does Dementia Have To Do With This?

Abstract: BackgroundPatients in acute care hospitals no longer in need of acute care are called Alternate Level of Care (ALC) patients. This is growing and common all across Canada. A better understanding of this patient population would help to address this problem.MethodsA chart review was conducted in two hospitals in New Brunswick. All patients designated as ALC on July 1, 2009 had their charts reviewed.ResultsThirty-three per cent of the hospital beds were occupied with ALC patients; 63% had a diagnosis of dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 13 publications
5
65
0
Order By: Relevance
“…The estimates of the percent of ALC patients with dementia range between 25 % [46] to over 60 % [37]. The use of hospital beds for ALC patients can contribute to a decrease in acute care capacity, emergency department overcrowding, and patient flow inefficiencies throughout the entire healthcare system [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimates of the percent of ALC patients with dementia range between 25 % [46] to over 60 % [37]. The use of hospital beds for ALC patients can contribute to a decrease in acute care capacity, emergency department overcrowding, and patient flow inefficiencies throughout the entire healthcare system [47].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the impact of dementia on ALC days may be under-estimated in administrative-data based studies and underscores the complexity of these patients. Most ALC patients are waiting for placement in long-term care facilities [37, 48]. A study exploring ALC patients waiting for nursing home admission, however, found that some of these patients could be discharged to a community setting with the support of transitional programs and increased community care [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of only English-speaking patients who could provide informed consent precluded those with cognitive impairment or non-Anglophone from participating. A recent study conducted in the province where this study took place reported that 63.6% of people designated as ALC had a diagnosis of dementia (McCloskey et al 2014). It is possible that patients who did not meet this study' s eligibility criteria had very different experiences that are not reflected in these findings.…”
Section: Discussionmentioning
confidence: 88%
“…Others have attempted to explore possible strategies to respond and reduce ALC within Canadian hospitals (Costa and Hirdes 2010;Ontario Hospital Association 2012;Sutherland and Crump 2011;Walker 2011). Despite these efforts, ALC continues to be of concern, with reports of as many as 25% of acute care beds being occupied by people designated as ALC (McCloskey et al 2014).…”
Section: Résumémentioning
confidence: 99%